Development of a silicon strip detector for novel accelerators at SINBAD. (November 2019) - Jaster-Merz, S; Assmann, R W; Burkart, F; Dorda, U; Kraemer, U; Panofski, E; Stanitzki, M
Abstract: At the SINBAD facility (DESY Hamburg), novel particle acceleration techniques like dielectric laser acceleration (DLA) structures will be tested using the ARES linac. Due to the small size of these structures, the accelerated electron beams only have a very low (sub-pC) charge. To determine the energy distribution of these beams, a silicon strip detector for the ARES linac spectrometer is currently under development. This detector fulfils the requirements of high spatial resolution for low charge density beams. The detector consists of two 1 cm × 1 cm silicon strip sensors and readout components. The design of the detector, its components and an estimate of its behaviour for a specific electron beam distribution are presented and discussed.